Analisis Determinan Kualitas Audit: Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Arum Puji Lestari; Theresia Hesti Bwarleling (Jurnal Syntax Transformation, 2022)
Audit quality is whether or not the audit process is carried out by the auditor, in the sense that each audit process is carried out according to the Public Accounting Standards (SAP) or not. An auditor must be able to examine the company and provide objective evidence that describes the actual condition of the company. The purpose of this study was to analyze the effect of audit fees, foreign ownership, KAP rotation, and firm size on audit quality. The population used in this study is the cement, ceramic & porcelain, metal and chemical sub-sector companies listed on the Indonesia Stock Exchange in 2017-2019, which consists of 45 companies. The dataused collection techniquepurposive sampling and produced 72 samples. The data used is secondary data. The method used is descriptive statistical analysis and logistic regression analysis using the assistance program, namely IBM SPSS version 25. The results of this study indicate that audit fees have a significant effect on audit quality, where this is an indication that a low audit fee will potentially lead to a violation of the auditor’s code of ethics. Suggestions for further research, further researchers are expected to be able to increase the number of research samples and also estimate more and more recent years so that research can be produced better, and it is also expected to be able to increase the use of other industries so that they can compare the audit quality of each industry in the manufacturing company. listed on the Indonesia Stock Exchange